Respuesta :

MAMJ
Solving for a:

2a[tex] x^{4} [/tex]+[tex] x^{3} [/tex]-bx+5 = 4[tex] x^{4} [/tex]+[tex] x^{3} [/tex]-c[tex] x^{2} [/tex]+2x+5
Subtract 5 and [tex] x^{3} [/tex] from both sides:
2a[tex] x^{4} [/tex]-bx=4[tex] x^{4} [/tex]-c[tex] x^{2} [/tex]+2x
Add bx to both sides:
2a[tex] x^{4} [/tex]=4[tex] x^{4} [/tex]-c[tex] x^{2} [/tex]+2x+bx
Divide both sides by 2[tex] x^{4} [/tex]:
a = 4[tex] x^{4} [/tex]-c[tex] x^{2} [/tex]+2x+bx/2[tex] x^{4} [/tex]
Simplify:
a = 4[tex] x^{3} [/tex]-cx+2+b/2[tex] x^{3} [/tex]

Solving for b:

Begin by doing the same as for a by subtracting 5 and  [tex] x^{3} [/tex] from both sides. Again add bx to both sides to avoid having to work with negatives. You should now have 2a[tex] x^{4} [/tex]=4[tex] x^{4} [/tex]-c[tex] x^{2} [/tex]+2x+bx.
Subtract 4[tex] x^{4} [/tex] and 2x from both sides as well as adding c[tex] x^{2} [/tex] to both sides:
 2a[tex] x^{4} [/tex]-4[tex] x^{4} [/tex]+c[tex] x^{2} [/tex]-2x=bx
Divide both sides by x:
b = 2a[tex] x^{4} [/tex]-4[tex] x^{4} [/tex]+c[tex] x^{2} [/tex]-2x/x
Simplify:
b = 2a[tex] x^{3} [/tex]-4[tex] x^{3} [/tex]+cx-2

Solve for c:

Begin again by subtracting 5 and [tex] x^{3} [/tex] from both sides. Next add c[tex] x^{2} [/tex] to both sides to again avoid working with negatives:
2a[tex] x^{4} [/tex]-bx+c[tex] x^{2} [/tex]=4[tex] x^{4} [/tex]+2x
Subtract 2a[tex] x^{4} [/tex] and add bx to both sides:
c[tex] x^{2} [/tex]=4[tex] x^{4} [/tex]+2x-2a[tex] x^{4} [/tex]+bx
Divide both sides by [tex] x^{2} [/tex]:
c = 4[tex] x^{4} [/tex]+2x-2a[tex] x^{4} [/tex]+bx/[tex] x^{2} [/tex]
Simplify:
c = 4[tex] x^{3} [/tex]+2-2a[tex] x^{3} [/tex]+b/x